Predicting college adjustment and retention: the role of protective factors - Olivas, Nicole, author; Borrayo, Evelinn, advisor; Gingerich, Karla, committee member; Richards, Tracy, committee member; Zimmerman, Toni, committee member (Colorado State University. Libraries, 2020)
The goal of the present study was to investigate which protective factors contribute to college success, as defined by social, emotional, and academic adjustment. Further, the study aimed to assess whether college adjustment in the first semester predicts academic success, retention, and college satisfaction after two years. In particular, the study assessed how males and females compare regarding the association of protective factors and college adjustment outcomes. One-hundred-sixteen participants completed the study, which included completing a set of surveys at three time points. This study found that individual, familial, and community protective factors predicted successful college adjustment at the beginning and end of the first semester of the first year in college. These findings suggest that qualities within the individual, family, and community support initial college adjustment and adjustment over time. The study found that adjustment at the end of first semester did not predict retention, GPA, or satisfaction with the college experience at the end of second year. It is possible that adjustment during the first semester has less of an impact on long-term success than originally thought. Finally, males and females appeared to have similar adjustment outcomes during the first two years of college. Although males reported greater personal talent, self-esteem, and coping self-efficacy than females, there were no gender differences in adjustment outcomes, which supports the gender similarities hypothesis. Future research should assess whether differences in college adjustment outcomes exist between first-generation and non-first-generation students.
Keywords: gender differences; retention; protective factors; college adjustment